A.D.A.M. student atlas of anatomy - Olson, Todd R. 4 0 16; Pawlina, Wojciech; 5 (Baltimore, Maryland : Williams & Wilkins, 1996)
Contains illustrative art, cadaveric photographs, radiographs, and tables designed to help expand a student's appreciation for and understanding of the essentials of human anatomy.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Atlases.;atlases.;Atlases. -- Human anatomy;Anatomy;Human anatomy; 20; 2